Diagnostic accuracy of circulating free DNA testing for the detection of KRAS mutations in non-small cell lung cancer: A systematic review and meta-analysis - Palmieri, Maria; Zulato, Elisabetta; Wahl, Sissel Gyrid Freim; Guibert, Nicolas; Frullanti, Elisa (Frontiers in Genetics, 2022)
Kirsten rat sarcoma viral oncogene homolog (KRAS) gene encodes a small GTPase that functions as a molecular switch in signal transduction, influencing cell proliferation. Mutations in KRAS gene represent important biomarkers for NSCLC target therapy. However, detection of KRAS mutations in tissues has shown obvious limitations. During the last years, analyses of circulating free DNA (cfDNA) is emerged as an alternative, minimally invasive, approach to investigate tumor molecular changes. Here, we assessed the diagnostic performance of cfDNA analysis, compared to tissues through a meta-analysis and systematic review of existing literature. From 561 candidate papers, we finally identified 40 studies, including 2,805 NSCLC patients. True-positive (TP), false-positive (FP), false-negative (FN), and true-negative (TN) values were extracted. Pooled sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), and diagnostic odds ratio (DOR), each with 95% CI, were calculated. A summary receiver operating characteristic curve (SROC) and area under curve (AUC) were used to evaluate the overall diagnostic performance. The pooled sensitivity was 0.71 (95% CI 0.68-0.74) and the specificity was 0.93 (95% CI 0.92-0.94). The diagnostic odds ratio was 35.24 (95% CI 24.88-49.91) and the area under the curve was 0.92 (SE=0.094). These results provide evidence that detection of KRAS mutation using cfDNA testing is of adequate diagnostic accuracy thus offering to the clinicians a new promising screening test for NSCLC patients.